2012
DOI: 10.2119/molmed.2012.00027
|View full text |Cite
|
Sign up to set email alerts
|

Neural Signaling in the Spleen Controls B-Cell Responses to Blood-Borne Antigen

Abstract: Entry of blood-borne pathogens into the spleen elicits a series of changes in cellular architecture that culminates in the systemic release of protective antibodies. Despite an abundance of work that has characterized these processes, the regulatory mechanisms that coordinate cell trafficking and antibody production are still poorly understood. Here, marginal zone (MZ) B cells responding to streptococcus in the blood were observed to migrate along splenic nerves, arriving at the red pulp venous sinuses where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
1
45
0
1
Order By: Relevance
“…The role of cholinergic neurotransmission is less clear; however, studies have shown that application of acetylcholine modifies splenic volume and blood flow in a sympathomimetic manner in isolated spleen (Felten et al, 1985; Reilly, 1985). Recently, it was also shown that the migration and activation of B-cells in the spleen are regulated by the vagus nerve activity (Mina-Osorio et al, 2012). In our study, fluorescent fibers that we found in the spleen traveled along and often remained associated with periarteriolar TH-positive fibers, thus supporting the model of cooperative action of cholinergic and noradrenergic endings in controlling the splenic vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of cholinergic neurotransmission is less clear; however, studies have shown that application of acetylcholine modifies splenic volume and blood flow in a sympathomimetic manner in isolated spleen (Felten et al, 1985; Reilly, 1985). Recently, it was also shown that the migration and activation of B-cells in the spleen are regulated by the vagus nerve activity (Mina-Osorio et al, 2012). In our study, fluorescent fibers that we found in the spleen traveled along and often remained associated with periarteriolar TH-positive fibers, thus supporting the model of cooperative action of cholinergic and noradrenergic endings in controlling the splenic vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pharmacological administration of nicotinic receptor agonists reduces the severity of systemic endotoxemia (Pavlov et al, 2007) and various animal models of inflammation of the intestines and pancreas (Galitovskiy et al, 2011; Ghia et al, 2008; van Westerloo et al, 2005). Likewise, electrical stimulation of the efferent vagus nerve, whose primary neurotransmitter is acetylcholine, mimics the antiinflammatory actions of nicotinic receptor agonists in the above experimental models of inflammation (Borovikova et al, 2000; Meregnani et al, 2011; Mina-Osorio et al, 2012; Wang et al, 2003). In support of a direct immunomodulatory action of acetylcholine signaling in immune cells, lymphocytes and macrophages have been found to express nicotinic acetylcholine receptors (Fujii et al, 2008; Kikuchi et al, 2008; Wang et al, 2003).…”
mentioning
confidence: 99%
“…Interestingly, stimulation of afferent vagus nerve fibers also has protective effects in this model, which suggests other brain-mediated mechanisms (98). Functional integration of the vagus nerve and splenic nerve is also implicated in the regulation of adaptive immune responses and B cell antibody production in the spleen during Streptococcus pneumonia (121) and in controlling T cell activation and egress from the spleen in experimental hypertension (122). Further molecular mapping of these circuits using genetic approaches (120) will advance understanding of their functional organization and indicate new therapeutic approaches.…”
Section: Functional Neuroanatomy For Communication With the Immune Symentioning
confidence: 99%
“…Consequently, acetylcholine acts on the α7 nAChRs on macrophages in the spleen and suppresses TNF production. Vagus nerve–splenic nerve signaling is implicated in the regulation of adaptive immune responses [59]. VNS in Streptococcus pneumonia suppresses the normal migration of B cells to the splenic red pulp, where they become antibody-secreting cells, by retaining the cells in the marginal zone, and decreases B cell antibody production.…”
Section: A Close Look At the Efferent Vagus Nerve Immunoregulatorymentioning
confidence: 99%
“…VNS in Streptococcus pneumonia suppresses the normal migration of B cells to the splenic red pulp, where they become antibody-secreting cells, by retaining the cells in the marginal zone, and decreases B cell antibody production. Splenic nerve transection significantly abolishes the migration arrest and results in reorganization of lymphoid architecture [59]. These and other studies in the context of endotoxemia, sepsis, inflammatory bowel disease [29,30,32] and other inflammatory conditions have triggered a great deal of interest in the vagus nerve-splenic nerve signaling in immune regulation.…”
Section: A Close Look At the Efferent Vagus Nerve Immunoregulatorymentioning
confidence: 99%